Open Doors by Fair Means: a quasi-experimental controlled study on the effects of an open-door policy on acute psychiatric wards - Lisa K. Schreiber; Florian G. Metzger; Erich Flammer; Heike Rinke; Andreas J. Fallgatter; Tilman Steinert (BMC, 2022)
Abstract Background Psychiatric wards treating involuntarily admitted patients are traditionally locked to prevent absconding. However, on the basis of observational evidence, the necessity for locked units in psychiatric hospitals has increasingly been questioned. Updated Mental Health Laws in several Federal States of Germany legitimate involuntary commitment without generally locked doors. Methods We examined the effects of an open-door policy in a quasi-experimental, prospective design. For the first time, at each of two locations, two identical wards serving as control and intervention could be compared. After a baseline period of three months, one ward at each location started the 12 month intervention period with the implementation of an open-door policy, while the respective control ward, as before, used open doors only facultatively. Primary outcomes were average opening times of the four wards between 8 a.m. and 8 p.m., and the number of involuntary treatment days with the doors open. Secondary outcomes were adverse events including aggressive incidents, absconding, suicide attempts and coercive measures. Results Overall, door-opening times increased significantly at both sites´ intervention wards. The number of adverse events did not increase during intervention period. Frequencies of coercive measures decreased in Friedrichshafen and remained unchanged in Tuebingen. In case of the intervention ward in Friedrichshafen, doors were open in up to 91% of all involuntary treatment days, whereas in the control ward, this was only the case in 67% of all involuntary treatment days (p < .001). In case of the intervention ward in Tuebingen, 45% of involuntary treatment days had open doors, compared to 30% in the control ward (p < .001). Conclusions It is possible to manage psychiatric wards with open doors without taking inappropriate risks. The extent to which open-door policies are achievable is be dependent on staffing and patient characteristics. Further research is necessary to explore the role of staff attitudes. Trial registration Our trial "Open Doors by Fair Means" is retrospectively registered with DRKS ( DRKS00015154 ) on Sept. 10th 2018 and displayed on the public web site. It is searchable via its meta-registry ( http://apps.who.int/trialsearch/ ).